1997
DOI: 10.1118/1.598117
|View full text |Cite
|
Sign up to set email alerts
|

The determination of dose characteristics of ruthenium ophthalmic applicators using radiochromic film

Abstract: Ruthenium ophthalmic applicators are energetic beta ray sources, supplied in several shapes and dimensions, and used in intraocular tumor therapy. Because of their small dimensions, the determination of dosimetric characteristics represents a technical challenge. We developed a semiautomatic method to define surface dose, dose distribution, and percentage depth dose of such applicators using radiochromic dosimetric media. These detectors consist of a thin (7 microns) radiation sensitive layer on polyester base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 15 publications
(9 reference statements)
2
47
0
2
Order By: Relevance
“…Mourtada et al 17 performed a comparative dosimetric analysis of 106 Ru/ 106 Rh ophthalmic brachytherapy and external beam proton therapy. The relative dose distributions for both treatment modalities were calculated in a model eye using the MCNPX MC code for the CCB applicator, yielding contradictory results: the MC-NPX calculations were consistent with the results obtained by Cross et al 16 using MCNP4B and by Taccini et al 9 using GEANT3, whereas the differences found by Cross et al 16 between MCNP4B and ACCEPT 3.0 were similar to those found among MCNPX, ACCEPT 3.0, and Soares et al's 5 film data.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Mourtada et al 17 performed a comparative dosimetric analysis of 106 Ru/ 106 Rh ophthalmic brachytherapy and external beam proton therapy. The relative dose distributions for both treatment modalities were calculated in a model eye using the MCNPX MC code for the CCB applicator, yielding contradictory results: the MC-NPX calculations were consistent with the results obtained by Cross et al 16 using MCNP4B and by Taccini et al 9 using GEANT3, whereas the differences found by Cross et al 16 between MCNP4B and ACCEPT 3.0 were similar to those found among MCNPX, ACCEPT 3.0, and Soares et al's 5 film data.…”
Section: Introductionmentioning
confidence: 61%
“…In the only available study providing dosimetric data on CIB applicators, which was performed by Taccini et al, 9 the authors measured the dose distributions for a number of applicator models using radiochromic film. For the CIB applicator, they reported isodose distributions in a plane perpendicular to the central axis at a 4.5 mm depth.…”
Section: H Cib/cib-2 Applicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison at some relevant incident energies of the calculated elastic (IAM-SCAR) and elastic þ rotational (IAM-SCARD) DCS for tetrahydrofuran to experimental results from Milosavljević et al (2005), Allan (2007), Colyer et al (2007 and Dampc et al (2007), theoretical data from Winstead and McKoy (2006), and our recommended values . by other authors with the Monte Carlo codes PENELOPE, MCNP, and GEANT3 (see Sá nchez-Reyes et al, 1998;Cross et al, 2001;Taccini et al, 1997), indicating that the set of CS and the energy loss distribution chosen by us caused a relatively higher energy deposition in greater depths.…”
Section: Application Examplesmentioning
confidence: 95%